ICT skills and employment: A randomized experiment - Mariana Blanco; Florencia Lopez Boo (Institute for the Study of Labor (IZA), 2010)
The aim of this paper is to evaluate the impact that the acquisition of Information and Communication Technologies (ICT) skills has on the labor market of two Latin-American cities: Buenos Aires and Bogota. Using cross-sectional data from an experiment that randomly assigned the ICT skills line in the resume, we assess the returns to ICT skills. For that, we submit approximately 11,000 fictitious Curricula Vitae (CVs) for real job vacancies published daily in the main job search engines in both cities. We estimate a binary choice model to identify differences in callbacks depending on ICT skills. We also analyze how gender, place of residence and occupational categories interact with ICT skills. Our econometric analysis supports previous literature suggesting that ICT skills could increase the probabilities of inclusion in the labor market, mainly for those at some level of disadvantage. To the best of our knowledge, this is the first study that quantifies the effect of ICT skills on employment. Our findings suggest that having ICT skills in the resume can increase the probability of receiving a callback by around 1 percent or more. This effect is much stronger in Bogota than in Buenos Aires, which suggests that ICT could be acting differently depending on the characteristics of the labor market.
Keywords: J23; J24; 330; Information and Communication Technologies; hiring decisions; labor demand